USE OF CHRYSANTELLUM AMERICANUM ( L.) VATKE AS SUPPLEMENT - Ferrara, Lydia (European Scientific Journal, ESJ, 2013)
The Chrysantellum americanum (L.) Vatke is a plant belonging to the family of Compositae long used in traditional medicine as hepatoprotector, biliary drainage, analgesic, rheumatic pains and kidney, as vasoprotector capillary and venous endothelium.The analysis of the protein fraction of Chrysantellum americanum (L.)Vatke revealed a content of crude proteins determined by the method of Kjeldahl equal to 10%. After acid hydrolysis of proteins, by GC-MS, were identified fifteen amino acids: glycine, valine, leucine, isoleucine, proline, methionine, serine, threonine, phenylalanine, aspartic acid, glutamic acid, arginine, lysine, histidine, tyrosine, and also the GABA The action tonic, hepatoprotective, lipidlowering and venotropic of phytocomplex also makes it suitable as a supplement to the established tolerability devoid of toxic and teratogenic effects